Board Characteristics and Earnings Management: Empirical Analysis of UK Listed Companies - LUO, JIESI (2017)
This study is going to find out the associations between characteristics of the boards and the level of earnings management. Moreover, the abnormal accruals are considered as the proxy of the level of earnings management, and which show the level of earnings management for the companies. This study uses Modified-Jones model to measure the abnormal accruals, and uses Random effects model to find out whether the characteristics of the boards are related with the level of earnings management. By running the regression, it finds out that the CEO duality and board size are negatively related the level of earnings management at the significant level. However, the study fails to find out the board meetings, percentage of independent directors and the percentage of female directors in the board is significantly associated with the level of earnings management.